On the Creation of New Network Language in Recent Years - Lidan Zhang (Journal of Linguistics and Communication Studies, 2024)
Information age network language has become the people show communication outside a very important language output, and the language of network language innovation is growing, through the 17 network new word technique of analysis, they according to the different words of classification, and further explore the function of different words. “Method of metaphor”, “homophonic word method”, “dialect borrowing” and “analogy of word method” are often used, with the function of humor, hint and irony. The reasons for making these words include their role in the emotional extension of words, their social environmental influences, and their connection with the environment and function of the network context.